Isorhamnetin attenuates osteoarthritis by inhibiting osteoclastogenesis and protecting chondrocytes through modulating reactive oxygen species homeostasis. Issue 6 (14th April 2019) - Zhou, Feng; Mei, Jingtian; Yuan, Kai; Han, Xiuguo; Qiao, Han; Tang, Tingting
Abstract: Increasing evidence indicates that osteoarthritis (OA) is a musculoskeletal disease affecting the whole joint, including both cartilage and subchondral bone. Reactive oxygen species (ROS) have been demonstrated to be one of the important destructive factors during early‐stage OA development. The objective of this study was to investigate isorhamnetin (Iso) treatment on osteoclast formation and chondrocyte protection to attenuate OA by modulating ROS. Receptor activator of nuclear factor‐kappa B ligand (RANKL) was used to establish the osteoclast differentiation model in bone marrow macrophages (BMMs) in vivo. H2 O2 was used to induce ROS, which could further cause chondrocyte apoptosis. We demonstrated that Iso suppressed RANKL‐induced ROS generation, which could mediate osteoclastogenesis. Moreover, we found that Iso inhibited osteoclast formation and function by suppressing the expression of osteoclastogenesis‐related genes and proteins. We proved that Iso inhibited RANKL‐induced activation of mitogen‐activated protein kinase activation of mitogen‐activated protein kinase (MAPK), nuclear factor‐kappa B (NF‐κB) and AKT signalling pathways in BMMs. In addition, Iso inhibited ROS‐induced chondrocyte apoptosis by regulating apoptosis‐related proteins. Moreover, Iso was administered to an anterior cruciate ligament transection (ACLT)‐induced OA mouse model. The results indicated that Iso exerted beneficial effects on inhibiting excessive osteoclast activity and chondrocyte apoptosis, which further remedied cartilage damage. Overall, our data showed that Iso is an effective candidate for treating OA.